Untangling the Influence of Heat Stress on Crop Phenology, Seed Set, Seed Weight, and Germination in Field Pea (Pisum sativum L.) - Lamichaney, Amrit; Parihar, Ashok K.; Hazra, Kali K.; Dixit, Girish P.; Katiyar, Pradip K.; Singh, Deepak; Singh, Anil K.; Kumar, Nitin; Singh, Narendra P. (Frontiers in Plant Science, 2021)
The apparent climatic extremes affect the growth and developmental process of cool-season grain legumes, especially the high-temperature stress. Present study aimed to investigate the impacts of high-temperature stress on crop phenology, seed set and seed quality parameters, which are uncertain in tropical environments. Therefore, a panel of 150 field pea genotypes, grouped as early (n=88) and late (n=62) maturing, were exposed to high-temperature environments following staggered sowing[normal sowing time or no heat-stress environment (NHSE); moderately-late sowing (15 days after normal sowing) or heat-stress environment-I (HSE-I); very-late sowing (30 days after normal sowing) or HSE-II]. The average maximum temperature during flowering was about 22.5±0.17oC for NHSE and increased to 25.9±0.11ºC and 30.6±0.19ºC in HSE-I and HSE-II. The average maximum temperature during the reproductive period (flowering to maturity) was in the order, HSE-II (33.3±0.03ºC)>HSE-I (30.5±0.10ºC)>NHSE (27.3±0.10ºC). The high-temperature stress reduced the seed yield (24-60%) and seed germination (4-8%) with a prominent effect on long-duration genotypes. The maximum reduction in seed germination (>15%) was observed in HSE-II for genotypes with>115 days maturity duration which was primarily attributed to higher ambient maximum temperature during the reproductive period. Under heat stress environments, the reduction in the reproductive period in early and late maturing genotypes was 13-23% and 18-33%, suggesting forced maturity for long-duration genotypes under late sown conditions. The cumulative growing degree-day at different crop stages had significant associations (p< 0.001) with seed germination in both early and late maturing genotypes and the results further demonstrate that an extended vegetative period could enhance the 100-seed weight and seed germination. Reduction in seed set (7-14%) and 100-seed weight (6-16%) was observed under heat stress environments, particularly in HSE-II. The positive associations of 100-seed weight were observed with seed germination and germination rate in the late-maturing genotypes, whereas, in early maturing genotypes negative association was observed for 100-seed weight and germination rate. The GGEBiplot analysis identified IPFD 11-5, Pant P-72, P-1544-1 and HUDP11 as superior genotypes as they possess an ability to produce more viable seeds under heat stress conditions. Such genotypes will be useful in developing field pea varieties for quality seed production under high-temperature environments.